The Integration of Green Chemistry Principles into Small Scale Chemistry Practicum for Senior High School Students - Listyarini, R. V.; Pamenang, F. D. N.; Harta, J.; Wijayanti, L. W.; Asy'ari, M.; Lee, W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Implementation of Principles of Green Chemistry in teaching chemistry can become an essential approach to enhance students’ awareness of the environmental problem. In contrast with the goal of sustainability, chemistry practicum normally deals with chemicals and waste management which contribute to environmental problem. A shift toward more sustainable and economical experiments is essential to maintain the existence of the practicum in the senior high curriculum. Small Scale Chemistry (SSC) practicum is one of the approaches to promote sustainability in chemistry practicum by using smaller scale and safer apparatus. It is expected to produce less waste. It is also safer and more economical chemistry experiment. This research aims to study the integration of principles of green chemistry in chemistry practicum by using SSC experiment. This study investigates two main topics in senior high school chemistry subject: electrochemistry and acid-base indicator. This study has shown the practice of integration of the principles of green chemistry approach into senior high school chemistry practicum through SSC. The experiments demonstrated in this study enable us to integrate Principles of Green Chemistry in terms of preventing waste, using less hazardous chemical, and conducting safer experiments which can be implemented in senior high school chemistry practicum.